The Ruling of Selling Debt by Debt in Islamic Law - A Comparative Jurisprudence Study - - Edress, Abdallah Ali (Journal of Islamic Sciences, 2020)
The research investigated the topic of "debt by debt sale" from a jurisprudential perspective. The opinions of the jurists, their evidence and suspicions about this type of sale were collected. The opinions of many contemporary jurists that it is permissible to sell debt for debt are discussed and refuted The research concludes that debt for debt sale is not valid as many contemporaries claim. It contravenes the consensus of jurists on its prohibition and the invalidity of their arguments and their failure to advance it in contravention of the evidence of the jurists and their unanimity on the prohibition of selling debt for debt. The study also explains the wisdom behind the prohibition of selling debt by debt, in terms of its relationship to gambling, the existence of ambiguity, and occupying the debts of the two parties without interest or benefit. This sale contravenes the legitimate purpose of the contracts, which is the profit.